Discovery of cold-active protease from psychrophilic bacteria isolated from Antarctic region for bio-prospecting - Muhammad Asyraf Abd Latip,; Siti Aisyah Alias,; Smykla, Jerzy; Faridah Yusof,; Mohd Azrul Naim Mohamad,; Noor Faizul Hadry Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The Antarctic region is a new frontier as natural sources for bio-prospecting purposes. Its extreme cold temperature may provide unique enzyme characteristics that have valuable potential for industrial and biotechnological applications. This study was designed to discover proteases that are activate and can work at very low temperatures. Soil samples from the Antarctic region were screened for protease activity on skim milk agar at 4°C. Bacteria that showed clear halo zone around the colonies were selected and identified through 16S rDNA sequencing. Out of 35 bacteria, 10 bacteria that showed rapid halo zone formation were selected and further analyzed by enzymatic assay. By using azocasein as a substrate, the reaction was measured using spectrophotometer at OD340 nm. Based on the 16S rDNA sequence, phylogenetic analysis showed that 88% of the bacteria producing protease were from Pseudomonas sp., 9% from Arthrobacter sp. and 3% from Paenibacillus sp. For enzymatic assay analysis, sample SC8 showed the highest protease activity compared to other 10 samples. This preliminary study successfully demonstrated cold active protease producers that can be further investigated for bioprospecting. In future, purification and characterization of this enzyme is required in order to optimize the enzyme activity.